A Dangerous Subject: The Fashion Model and the Beauty/Narcissism Double Bind. (9th February 2017) - Neumann, Cecilie Basberg
Abstract : In the wake of modernity, women's sexuality was positioned in a way that created a beauty/narcissism double bind that is still with us today. My concern in this article is that the subject position of "fashion model" serves as a constant reminder of this split, which is directed at all women and weakens the generalized woman's political agency. Fashion models themselves experience harassment and humiliation as well as pleasure and desire in their work as fashion models. However, the small portion of feminist work that has engaged explicitly with the fashion‐model business sees it mainly as an enterprise that is alienating and hostile to women. Although I do not entirely disagree with this analysis, it neglects the meaning of beauty and what beauty does to us with regard to creativity and pleasure. I wish to explore how some of the work experience of fashion models intersects with and challenges the beauty/narcissism double bind. I suggest that rather than grounding our understanding of the subject position "fashion model" and the fashion business solely in their reinforcement of the beauty/narcissism double bind, we should pay attention to the importance of what beauty and aspects of narcissism may mean.